2021
DOI: 10.3390/biomedicines9050553
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Vascular Biomarker Profiling in Elective Surgery Patients Developing Postoperative Delirium: A Prospective Cohort Study

Abstract: Background: Postoperative delirium (POD) ranks among the most common complications in surgical patients. Blood-based biomarkers might help identify the patient at risk. This study aimed to assess how serum biomarkers with specificity for vascular and endothelial function and for inflammation are altered, prior to or following surgery in patients who subsequently develop POD. Methods: This was a study on a subcohort of consecutively recruited elective non-cardiac as well as cardiac surgery patients (age > 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Immunoassay kit, human by request; Panomics Inc., Fremont, CA, USA) according to manufacturer protocol [20,21].…”
Section: Plos Onementioning
confidence: 99%
“…Immunoassay kit, human by request; Panomics Inc., Fremont, CA, USA) according to manufacturer protocol [20,21].…”
Section: Plos Onementioning
confidence: 99%
“…A striking observation in our study is the similarities in proteomic signatures between cases and non-cases at baseline, despite a clear difference at postoperative day one. Previous studies have shown that POD cases are likely to be in heightened pre-operative inflammatory state [20,46,69,[81][82][83][84][85], which makes them more vulnerable to intraoperative stressors. In our study, similarities in the levels of identified biomarkers at baseline suggests otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…Other outcome measures: Postoperative sleep and rest-activity rhythm data from accelerometer watches will be assessed as an exploratory outcome measure. In addition, patients will be evaluated during the baseline interview with continuous ECG recording to explore heart rate response and vascular biomarkers associated with delirium 39 40. A four-lead ECG with oximetry will be placed on the patients by trained study staff during the inclusion visit.…”
Section: Methods and Analysismentioning
confidence: 99%